Economic convergence of the first and second moment in the provinces of Argentina - Marina, Adriana (Estudios de Economía, 2016)
The purpose of this paper is to study the inequality of income between the provinces of Argentina. The data in this paper comes from the traditionally used GDP p.c., as well as from Household survey. The analysis examines two separated but also related research areas, regional convergence and income distribution. Our results suggest that the provinces of Argentina seem to have a tendency towards the same level of income (wage convergence) and the same level of inequality.